The investigation of femtocell Home eNodeB (HeNB) propagation path loss model / Nurul Nadiah Khaseran and Amirudin Ibrahim - Khaseran, Nurul Nadiah; Ibrahim, Amirudin (Universiti Teknologi Mara Cawangan Pulau Pinang, 2017)
In order to overcome the problem of indoor mobile signal coverage as well as dealing with the signal reception from macro cells, femtocell is introduced. It is installed in a short service range by the subscribers, called as Home evolved Node B (HeNB) [1] There are four carrier frequencies used for Long Term Evolution (LTE), 850MHz, 1800 MHz, 2300MHz, and 2600 MHz. With the changes of criteria of the surrounding such as frequencies, distance, height and surrounding materials, the smaller the path loss value in indoor environment, the better the signal reception will be. Third Generation Partnership Project (3GPP) used TR36.814 with 2 GHz carrier frequency with different lengths and obstructions, however this frequency is not offered for LTE in Malaysia and some studies need to be done in order to find the one with the best signal reception. This resulted on how the number of wall layers play roles in an indoor environment. 850MHz was found out to be the best frequency out of the four LTE frequencies in Malaysia for different types of indoor environment.